Non-specific immune response of turbot, Scophthalmus maximus (L.), experimentally infected with a pathogenic Vibrio pelagius - Villamil, L.; Figueras Huerta, Antonio; Aranguren, Raquel; Novoa, Beatriz (Journal of Fish Diseases, 2003)
9 páginas, 5 figuras The effect of a pathogenic Vibrio pelagius, isolated during a mass mortality of turbot larvae, on the non-specific immune response of turbot, Scophthalmus maximus (L.), macrophages was studied both in vitro and in vivo. The in vitro treatment of head kidney (HK) macrophages with viable V. pelagius caused a significant inhibition of the chemiluminescence (CL) response in comparison with untreated macrophages, while incubation with heat-killed bacteria did not affect this response. In vivo, the intraperitoneal injection of V. pelagius resulted in a significant inhibition of the CL response in infected fish at days 1 and 4 post-infection compared with the control fish response. The HK macrophage nitric oxide (NO) production was enhanced by in vitro incubation with intermediate doses of viable V. pelagius (5 × 103 and 5 × 104 bacteria mL−1) and higher doses of the heat-killed bacteria (5 × 104–5 × 106 bacteria mL−1). In both cases, the NO inhibitorN-ω -nitro-L-arginine was capable of down-regulating the specific NO induction caused by incubation with the bacterial treatments. In contrast, incubation with ECPs at higher doses caused a reduction in NO production. In vivo, a significant enhancement in NO production was also observed in macrophage supernatants at day 10 post-infection. Lysozyme concentration in the serum was also significantly increased in the experimentally infected fish at days 4 and 10 post-injection. In addition, viable V. pelagius and its ECPs significantly reduced HK macrophage viability in vitro, whereas no significant differences in viability were observed during the incubation with heat-killed bacteria. As NO production was enhanced in the experimentally infected fish, the inhibitory effect of the NO donor, S-nitroso-acetyl-penicillamine (SNAP), was tested in vitro in a cell-free assay. The results showed that growth of V. pelagius was significantly inhibited using SNAP at a high concentration (1 mm). This work was partially supported by project 1FD97-0044-C03-03 from ...